Immediate Effect of Kinesio Taping Application on Joint Proprioception Function in Knee Osteoarthritis Patients - Inggar Narasinta; Reni Hendrarati Masduchi; Patricia Maria Kurniawati (Surabaya Physical Medicine and Rehabilitation Journal, 2019)
Background: Osteoarthritis (OA) is the most common form of arthritis. Pathologic process of osteoarthritis are changes of joint structures and surrounding structures. Injury on articular structure cause mechanical disturbance and reduce joint sensation. Proprioception has an important role in joint stabilization through sensorimotor system. Decrease of proprioception lead to decrease of functional ability on OA patients. Kinesio taping (KT) is one option of therapy in musculoskeletal injury.  Kinesio taping can reduce pain and inflammation, facilitate muscle activity and stimulate mechanoreceptor. This study aimed to evaluate the effect of KT application on proprioception in knee OA patients.Method: This study was an experimental pre-post study. We measured the proprioception function of eight participants with knee OA (mean age 59,3 ± 6,22 years) before and 30 minutes after KT application. Joint position sense (JPS) and time to detect passive movement (TTDPM) using Cybex Isokinetic Dynamometer were used as proprioception function measurement. Technique of KT used was superior and inferior Y with 25% stretch.Result: All of JPS and TTDPM from 8 participants, before and 30 minutes after KT application, both on affected and unaffected sides, showed no significant difference (p>0.05).Conclusion: Kinesio taping with superior and inferior Y 25% stretch did not improve JPS and TTDPM in knee OA patients.